1996
DOI: 10.1038/bjc.1996.205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of staurosporine and four analogues: their effects on growth, rhodamine 123 retention and binding to P-glycoprotein in multidrug-resistant MCF-7/Adr cells

Abstract: Summary The potent kinase inhibitor staurosporine and its protein kinase C (PKC)-selective analogue CGP 41251 are known to sensitise cells with the multidrug resistance (MDR) phenotype mediated by Pglycoprotein (P-gp) to cytotoxic agents. Here four PKC-selective staurosporine cogeners, CGP 41251, UCN-01, RO 31 8220 and GF 109203X, were compared with staurosporine in terms of their MDR-reversing properties and their susceptibility towards P-gp-mediated drug efflux from MCF-7/Adr cells. Staurosporine was the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 18 publications
6
33
0
Order By: Relevance
“…27 Although enhanced expression of Pgp has been shown to reduce, albeit weakly, uptake of small molecule inhibitors such as flavopiridol, 47 it has been found to be somewhat more effective in diminishing the toxicity of UCN-01 in MCF-7 breast cancer cells. 48 However, the finding that Dox40 MM cells were fully sensitive to UCN-01/PD184352 toxicity argues that Pgp-related mechanisms do not play a major role in determining the response of MM cells to either of these agents. Resistance of MM.1R cells to dexamethasone has been attributed to a mutation in the steroid receptor.…”
Section: Discussionmentioning
confidence: 89%
“…27 Although enhanced expression of Pgp has been shown to reduce, albeit weakly, uptake of small molecule inhibitors such as flavopiridol, 47 it has been found to be somewhat more effective in diminishing the toxicity of UCN-01 in MCF-7 breast cancer cells. 48 However, the finding that Dox40 MM cells were fully sensitive to UCN-01/PD184352 toxicity argues that Pgp-related mechanisms do not play a major role in determining the response of MM cells to either of these agents. Resistance of MM.1R cells to dexamethasone has been attributed to a mutation in the steroid receptor.…”
Section: Discussionmentioning
confidence: 89%
“…PKC activators also increased drug accumulation and decreased drug sensitivity in MCF-7/Adr (Fine et al, 1988) and KM12L4a cells (Dong et al, 1991), and induced MDRJ gene expression in normal human lymphocytes (Chaudhary and Roninson, 1992). Conversely, a variety of PKC inhibitors, such as staurosporine (Sato et al, 1990), the staurosporine analogues CGP 41251 (Utz et al, 1994; Budworth et al, 1996) and GF 109203X , calphostin C (Bates et al, 1993) and safingol (Sachs et al, 1995), reversed P-gp-mediated mdr. However, reversal of drug resistance caused by staurosporine analogues is probably associated with direct interaction with P-gp rather than with PKC inhibition (Smith and Zilfou, 1995;Gekeler et al, 1996;Goodfellow et al, 1996;Budworth et al, 1996).…”
mentioning
confidence: 99%
“…Conversely, a variety of PKC inhibitors, such as staurosporine (Sato et al, 1990), the staurosporine analogues CGP 41251 (Utz et al, 1994; Budworth et al, 1996) and GF 109203X , calphostin C (Bates et al, 1993) and safingol (Sachs et al, 1995), reversed P-gp-mediated mdr. However, reversal of drug resistance caused by staurosporine analogues is probably associated with direct interaction with P-gp rather than with PKC inhibition (Smith and Zilfou, 1995;Gekeler et al, 1996;Goodfellow et al, 1996;Budworth et al, 1996). The aim of this study was to investigate the link between PKC and mdr by analysis of changes in expression of the PKC and MDR] genes in drug-selected mdr cells, cultured without the selective pressure of drug in the medium.…”
mentioning
confidence: 99%
“…Our data shed further light on the complexity of substrate interactions with ABCB1 adding to previous reports that had suggested that the mode and/or strength of ABCB1 interaction may differ among ABCB1 substrates [25][26][27][28][29][30]. Notably, the composition of the cell membrane and ABCB1 polymorphisms/ mutations are also known to modulate ABCB1 function and substrate specificity [23;31].…”
Section: Discussionmentioning
confidence: 80%